2021
DOI: 10.3390/ani11010214
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Positive Human Contact during Gestation on the Behaviour, Physiology and Reproductive Performance of Sows

Abstract: Previous positive interactions with humans may ameliorate the stress response of farm animals to aversive routine practices such as painful or stressful procedures, particularly those associated with stockpeople. We studied the effects of positive handling by providing younger (parity 1–2) and older (parity 3–8) sows housed in pens of fifteen (n = 24 pens in total) with either positive human contact (+HC) or routine human contact (control) during gestation. The +HC treatment involved a familiar stockperson pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Daily positive handling, involving a feed reward, gentle touching of and softly talking to sows individually late in gestation, did not affect nesting behaviour and activity around parturition, nursing behaviour, farrowing duration, piglet mortality or piglet weight gain in comparison to routine human contact during this period (Andersen et al, 2006). Daily positive handling, involving daily patting and scratching of gestating sows in pens did not affect farrowing rate or the number of piglets born alive, stillborn or weaned in comparison to sows that received routine human contact (Hayes et al, 2021a).…”
Section: Space Nesting/foraging Materials and Group Lactationmentioning
confidence: 77%
“…Daily positive handling, involving a feed reward, gentle touching of and softly talking to sows individually late in gestation, did not affect nesting behaviour and activity around parturition, nursing behaviour, farrowing duration, piglet mortality or piglet weight gain in comparison to routine human contact during this period (Andersen et al, 2006). Daily positive handling, involving daily patting and scratching of gestating sows in pens did not affect farrowing rate or the number of piglets born alive, stillborn or weaned in comparison to sows that received routine human contact (Hayes et al, 2021a).…”
Section: Space Nesting/foraging Materials and Group Lactationmentioning
confidence: 77%
“…The quality of stockmanship is determined by the stockperson's personality, attitude, and behaviour ( 50 , 152 ), and has a substantial effect on stress levels in farm animals ( 49 , 50 ). Hayes et al ( 153 ) showed the potential for positive handling to reduce fear of humans in sows, while Dokmanovic et al ( 154 ) showed numerically lower cortisol concentrations in gently handled pigs, compared to those which were handled roughly. In contrast, Manteca and Jones ( 50 ), Hemsworth and Boivin ( 155 ) showed compromised reproductive performance resulting from rough handling and fear of humans in sows.…”
Section: Risk Factors For Chronic Stress In Pregnant Sowsmentioning
confidence: 99%
“…This in turn can be associated with intense acute stress ( 158 ) occurring intermittently and contributing to chronic stress ( 18 ). Poor stockmanship is therefore a potential risk factor for chronic stress, with known detrimental consequences for sows ( 153 ).…”
Section: Risk Factors For Chronic Stress In Pregnant Sowsmentioning
confidence: 99%
“…Repeated gentle contacts induce a decreased fear of humans and even an increased approach toward humans ( 92 ). Developing this good HAR prior to farrowing could help mitigate any potential safety issues post farrowing ( 99 , 100 ) and careful/considered handling of piglets post-farrowing also reduces fearfulness ( 69 , 101 ). Supporting the scientific evidence are reports by farmers about success factors for working with loose housed sows and the importance of stockperson' attitude toward the sows, their empathy toward them and the rewarding aspect of working with loose sows ( 18 ).…”
Section: Tier 2 Stakeholder Needs and Considerationsmentioning
confidence: 99%